Doppler measurements of both umbilical arteries do not improve predictive value for adverse perinatal outcomes in small-for-gestational age fetuses. (December 2018) - Vollgraff Heidweiller-Schreurs, Charlotte A.; van Maasakker, Ninieck E.; van de Ven, Peter M.; de Groot, Christianne J.M.; Bax, Caroline J.; de Boer, Marjon A.
Abstract: Objective: To assess agreement of Doppler ultrasound measurements of the two umbilical arteries in small-for gestational age (SGA) fetuses, and to compare discriminative ability between the two arteries for adverse perinatal outcome. Study Design: We analysed a prospective cohort of singleton SGA pregnancies, in which the pulsatility index (PI) of both umbilical arteries was standardly measured by Doppler ultrasound in the free-floating umbilical cord. The outcome of interest was a composite adverse outcome, defined as perinatal death, Apgar score <7 at 5 min, cesarean section for fetal distress, and neonatal intensive care unit admission. Results: A total of 531 measurements were performed in 124 patients. Mean absolute difference between PI measured in the two umbilical arteries was 0.14 (95% CI: 0.12 to 0.15), showing good agreement with an ICC of 0.830 (95% CI: 0.801 to 0.854). Perinatal outcomes were available for 101 patients, of which 48 patients (48%) had a composite adverse perinatal outcome. We found no significant differences between AUCs for prediction of an adverse outcome based on lowest, highest and mean PI values in the two umbilical arteries (AUCs = 0.75, 0.74, 0.75 with p = 0.91). As a comparison, the AUC of a PI value obtained in a single, randomly selected umbilical artery was 0.74. Conclusion: The two umbilical arteries show good agreement in terms of their PI values in the free-floating umbilical cord, and do not differ in terms of their discriminative ability for adverse perinatal outcome in SGA fetuses. We found no evidence of an added value of standard Doppler measurement of both umbilical arteries.